A Model-Based Approach of DC-DC Converters Dedicated to Controller Design Applications for Photovoltaic Generators - Labidi, Z. R.; Schulte, H.; Mami, A. (Engineering, Technology & Applied Science Research, 2019)
In this paper, a model-based approach of DC-DC converters dedicated to controller design applications for photovoltaic generators is introduced. The paper provides a mathematic averaging model, based on the state space method for DC-DC converters that is used as an adaptation level in photovoltaic generators. This modeling allows the dynamics of the system to be described by presenting a reliable model to be used for oriented controller design. The two most needed topologies of DC-DC converters are proposed, buck and buck-boost, and an overview of integral state feedback controller design using a model-based approach for a boost converter connected to a photovoltaic generator described in our previous published work is provided. The model-based conception of both converter types is analyzed for optimal use in control-oriented design. The validation of each model is demonstrated by comparative curves represented by a detailed plant model using simscape devices available and implemented in Simulink/Matlab.